IMPLEMENTASI PERATURAN BUPATI KABUPATEN SUMBAWA NO. 114 TAHUN 2022 TENTANG PENYELENGGARAAN PENDIDIKAN ANTI KORUPSI PADA SATUAN PENDIDIKAN DI KABUPATEN SUMBAWA - Aldi Apriansyah (Yayasan Nusantara Hasana Berdikari, 2025)
Regent Regulation No. 114 of 2022 is a derivative of NTB Governor Regulation No. 94 of 2022 concerning the Implementation of Anti-Corruption Education in NTB Province. The purpose of this program is to break the chain of corruption by means of anti-corruption education in schools. This study uses descriptive qualitative research methods and data collection techniques using observation, interview and documentation techniques. This study uses the theory of policy implementation from Ripley & Franklin. The results of the study show that many actors are involved in the success of this program consisting of the Regent, the Department of Education and Culture, to schools. The clarity of the objectives of this program is about corrupt behaviors that must be avoided. The development and complexity of this program speaks about the integrity of anti-corruption education inserted in each subject and about how it is implemented. as well as uncontrollable factors that influence its implementation, such as Human Resources, Budget, Coordination between Institutions to supervision and evaluation. The conclusion of this study speaks about the government's commitment to eradicating corruption as early as possible by providing an understanding of the dangers and impacts of corruption to school students.